Synthesis and characterization of mesoporous expanded graphite modified with PA/H3PO4 for enhanced oil sorption efficiency - Elbidi, Moammar; Mohd Salleh, Mohamad Amran; Gunam Resul, Mohamad Faiz Mukhtar; Rashid, Suraya Abdul (Springer Science and Business Media, 2023)
The global challenge of addressing oil spills in the ocean arises from their mobility and limited self-purification capacity, resulting in substantial and enduring harm to aquatic ecosystems and the depletion of valuable resources. Expanded graphite (EG) is a versatile and useful material that offers various unique properties and has many practical uses in industry and commerce, specifically in oil spill clean-up. This article provides a sulfur-free EG modified by palmitic acid (PA) / phosphoric acid (H3PO4). EG was synthesized by a two-step chemical oxidation process, with natural graphite flake (NGF) serving as the precursor. The chemical intercalation procedure was carried out at room temperature for 30 min in the first step "oxidation" with an optimum weight ratio of 1 g: 5.1 g: 18.8 g: 0.2 of NGF, PA, H3PO4, and KMnO4. Then, in the second step "intercalation", nitric acid, acetic acid, and potassium permanganate were utilized as assistant intercalating agents to further enhance the expanded volume of EG. FT-IR, XRD, and SEM were used to investigate the functional groups, structures, and morphology of the EG. The findings demonstrated that the interlayers within the natural flake graphite were completely opened and transformed into a structure resembling a fluffy rope, resembling the shape of a worm, upon expansion. Under optimal conditions, the maximum volume expansion achieved was 470 mL/g. The mesoporous expanded graphite, modified with PA/H3PO4, exhibits promise as an engineering material for water purification sorbents and also demonstrates a noteworthy oil sorption capacity.